2012
DOI: 10.4137/bmi.s9060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ischemia-Modified Albumin and C-Reactive Protein in Type 2 Diabetics with and without Ketosis

Abstract: OverviewTo investigate whether serum ischemia-modified albumin or C-reactive protein is reliable for predicting type 2 diabetic patients with ketosis.ApproachOne hundred and four diabetic patients, 48 with diabetic ketosis, and 33 controls were enrolled in the study. Serum ischemia-modified albumin and C-reactive protein were measured and evaluated for their ability to distinguish diabetic ketosis.ResultsCompared to the controls, the ischemia-modified albumin and C-reactive protein levels were higher in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(44 reference statements)
3
13
1
Order By: Relevance
“…There are concerns about the tissue-specificity of IMA, it has been suggested that IMA is a biomarker for oxidative stress in ischemia or non-ischemia related disease. 28 In agreement with the present study, the IMA could be a risk biomarker for AD.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There are concerns about the tissue-specificity of IMA, it has been suggested that IMA is a biomarker for oxidative stress in ischemia or non-ischemia related disease. 28 In agreement with the present study, the IMA could be a risk biomarker for AD.…”
Section: Discussionsupporting
confidence: 93%
“…Ma et al found high levels of IMA in type 2 diabetic patients with ketosis, and determined a high correlation between IMA and CRP. 28 In the present study, we did not observed any correlations between the IMA and CRP, which might highlight the impact of oxidative stress on AD pathogenesis. Can et al observed high IMA values in AD patients, and they measured the IMA by colorimetric methods.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…18,19 IMA has been well accepted in the literature as a marker of OS, and its elevation has been associated with endothelial dysfunction, inflammation, and hyperglycemia in different types of diabetes with and without complications. [17][18][19][30][31][32][33][34] Hyperglycemia in DM is linked to OS, and retinal exposure to hyperglycemia activates multiple enzymes/ pathways accelerating OS and development of DR. [9][10][11]35 Hyperglycemia promotes increased IMA formation probably owing to mechanisms of hypoxia and OS. [17][18][19] Interestingly, it was reported that increased glycosylation of hemoglobin increases its affinity for oxygen, therefore, preventing its release at the tissue inducing hypoxia and OS.…”
Section: Discussionmentioning
confidence: 99%